2016 International Conference on Defects in Insulating Materials (ICDIM 2016). (February 2017) - Dujardin, C.; Homeyer, E.; Houel, J.; Ledoux, G.
Abstract : The 2016 edition of the International Conference on Defects in Insulating Materials (ICDIM 2016) was held in Lyon, France on July 10-15, 2016. A scientific community always originates from a common historical background and our common background is the science of color centers, which has been nicely reviewed by Prof. Heiz Pick in 1980 [1]. Because a scientific community always needs events to gather scientists from all around the world, setting up a conference series is fruitful way to regularly stimulate joint research and share recent advances. In this spirit, the first international event related to color center science was held in Argonne-USA in 1956. In 1973, a similar conference series entitled Europhysics Conference: Lattice defects in Ionic Crystals emerged in Europe (Marseille). In 1977, in Gatlingburg, the Colour Centre conference series became the first official International Conference on Defects in Insulating Materials and in 1994, in Lyon, the European meeting on Lattice Defects in Ionic Crystal merged with ICDIM and became EuroDIM. Both events occur every 4 years, leading to an event on materials defect science every 2 years. Figure 1 depicts the historical revue of the evolution of the ICDIM/EuroDIM conference series. Note that during ICDIM 2016, Dr. Martin Nikl and Prof. Rob Jackson have been elected as the chairperson of respectively ICDIM and EuroDIM conference series. Figure 1: the historical evolution of the 60 years of conferences on defects in insulating crystals This conference series is rather focused and aims to promote material sciences around defects, particularly in wide band gap crystals and glasses. But to adapt to the current trends, the content of the topics has evolved along the following items: -Point and extended defects -Phenomena at surfaces and interfaces -Low dimensional and nano-morphological systems -Defect modeling and computational methods -Luminescence of excitons, impurities and defects -Radiation induced defects and material damage -Scintillation, energy transfer and storage, carrier trapping -Laser actived centers and nonlinear optical phenomena -Disordered systems -Applied materials and interdisciplinary topics. This issue of the Institute Of Physics conference series is dedicated to papers submitted during the ICDIM 2016 event in Lyon, France. 209 abstracts were selected for oral or poster presentation, always in plenary session. We have also proposed 7 invited keynote speakers who presented didactical talks introducing their respective fields to young researchers. Most of the talks have been video recorded and can be seen on the following YouTube channel [2]. The International Committee has selected Guangzhou (China) for ICDIM 2020, which will be chaired by Prof. Mingying Peng. [1] H.Pick 1980, J. de Physique, Colloque C6, Tome 41, C6-1, Fifty years of colour centre physics [2]https://www.youtube.com/playlist?list=PL_ZZHWrfptdQPjO8Q9H6rOBkuFS7pbTBV Guest Editors Prof. C.Dujardin, Conference Chair and Senior Editor Dr. E.Homeyer, Associate Editor Dr. J.Houel, Associate Editor Dr. G.Ledoux, Associate Editor